Social focus on women - Whitmarsh, Alyson; Church, Jenny; Summerfield, Carol; Great Britain. Central Statistical Office (London HMSO, 1995)
This is the second in series of publications which paint a picture of different groups of people in contemporary society ; what it is like to be a women in the United Kingdom today.
At head of title: Central Statistical Office.
"ISSN 1355 5987"--T.p. verso.
Includes bibliographical references (pages 62-63) and index.
Keywords: Women -- Great Britain -- Social conditions -- Statistics